Ethiques du corps dans Antarctica de Claire Keegan - E. Vernadakis (Presses Universitaires de Caen, 2014)
A selection of stories from Claire Keeganʼs first collection Antarctica (1999) is here examined through the perspective of ethos. Each story, the author argues, illustrates the clash between two etymological meanings of ethos through a dramatic conflict between inherited practices and the idiosyncratic disposition of the characters (i.e. tradition vs. taste). The contrast is explored within a frame which brings together Camille Pagliaʼs theory of literature and the arts as an extension of the archaic connection between sexuality and religion and Judith Butlerʼs theory of performativity. Within this frame one of the storiesʼ major features is a taste for taking risks. Instead of putting the body at a distance for the mind’s sake, Keeganʼs stories seem to invite the reader to take the risk of exploring it (i.e. the body), even if such a risk may lead to death.